First Comparison of Hypothermic Oxygenated PErfusion Versus Static Cold Storage of Human Donation After Cardiac Death Liver Transplants: An International-matched Case Analysis. Issue 5 (November 2015) - Dutkowski, Philipp; Polak, Wojciech G.; Muiesan, Paolo; Schlegel, Andrea; Verhoeven, Cornelia J.; Scalera, Irene; DeOliveira, Michelle L.; Kron, Philipp; Clavien, Pierre-Alain
Abstract : Background: Exposure of donor liver grafts to prolonged periods of warm ischemia before procurement causes injuries including intrahepatic cholangiopathy, which may lead to graft loss. Due to unavoidable prolonged ischemic time before procurement in donation after cardiac death (DCD) donation in 1 participating center, each liver graft of this center was pretreated with the new machine perfusion "Hypothermic Oxygenated PErfusion" (HOPE) in an attempt to improve graft quality before implantation. Methods: HOPE-treated DCD livers (n = 25) were matched and compared with normally preserved (static cold preservation) DCD liver grafts (n = 50) from 2 well-established European programs. Criteria for matching included duration of warm ischemia and key confounders summarized in the balance of risk score. In a second step, perfused and unperfused DCD livers were compared with liver grafts from standard brain dead donors (n = 50), also matched to the balance of risk score, serving as baseline controls. Results: HOPE treatment of DCD livers significantly decreased graft injury compared with matched cold-stored DCD livers regarding peak alanine-aminotransferase (1239 vs 2065 U/L, P  = 0.02), intrahepatic cholangiopathy (0% vs 22%, P  = 0.015), biliary complications (20% vs 46%, P  = 0.042), and 1-year graft survival (90% vs 69%, P  = 0.035). No graft failure due to intrahepatic cholangiopathy or nonfunction occurred in HOPE-treated livers, whereas 18% of unperfused DCD livers needed retransplantation. In addition, HOPE-perfused DCD livers achieved similar results as control donation after brain death livers in all investigated endpoints. Conclusions: HOPE seems to offer important benefits in preserving higher-risk DCD liver grafts. Abstract : Supplemental Digital Content is available in the text